Pelatihan Pembuatan Kue Rasidah Sebagai Bentuk Mempertahankan Kuliner Khas Melayu Di Era Modern Desa Aras Sembilan. - Farhan Hafizh; Maulina Hayati; Annisa Nuri; Rani Febriyanni; Kamaliah (peduli riset dan pengabdian masyarakat, 2024)
Culinary is a part of life that is closely related to daily food consumption because everyone needs food to be able tocarry out daily activities because the source of energy and protein comes from food. Starting from simple food tohigh-class and luxurious food. All of this requires processing even though it is quality and nutritious. In thismodern era, many young people only know the name of a food without knowing the history and cultural value ofthe food itself. With this training, it is hoped that the community will be able to preserve traditional Malay foodagain. The method of implementing KKN service by STAI Jam'iyah Mahmudiyah Tanjung Pura students inAceh Tamiang in Aras Sembilan village, regarding the socialization of Rasidah cake making training as an effortto maintain typical Malay culinary delights to reintroduce them to society in the modern era. The existence of Rasidah cakes has existed since the heyday of the Malay kingdom. Rasidah cakes are one of the traditional foods,namely foods that have been preserved from generation to generation by the Malay tribe. Through this trainingoutreach, the KKN team from STAI Jam'iyah Mahmudiyah Tanjung Pura Langkat was able to design andimplement a program that not only focuses on preserving typical Malay culinary delights, but also preservingand reintroducing them to society in the modern era.